FAKTOR FUNDAMENTAL MAKRO DAN SKIM BUNGA KREDIT SEBAGAI VARIABEL INTERVENING PENGARUHNYA TERHADAP KINERJA BANK - Harmono Harmono (Jurnal Keuangan dan Perbankan, 2012)
This study aim to analysis the effect of macroeconomic fundamental and credit interest scheme to financialperformance of conventional Bank in Indonesia. The operational of dependent variable, by using Capital AdequacyRatio, non-performing loan, net interest margin, return on assets, and loan to deposits ratio. And theothers hand,independent variable are measured by macroeconomics fundamental;i.e.Interest Rate of IndonesianCentral Bank, inflation, and exchange rate of rupiah to US$.Credit interest scheme consist of working-capitalcredit interest rate, investment credit, and interest rate of consumption credit. Sampling technique,using purposivesampling and the number of samples is conventional banks in Indonesia. Data will be analysis 2006-2010monthly. Analysis technique isstructural equation model. The discovery results showed, the macroeconomicfundamental factors have significant to bank performance and dimension of credit interest scheme have role asintervening variable in supporting macro fundamental in influencing to financial performance of conventionalbanking in Indonesia. For represented of variables have any significant in contributed to each dimension can bedescribed, for macroeconomic fundamental, all variable is significant to contribute in factor construct. For creditinterest scheme was too all of variable, and bank performance just Capital Adequacy Ratio and Return on Assets.